The Influence of Peer Groups on The Academic Performance of University Students in Mathematics Courses - Mrope, Fadhili Mustafa; Kira, Ernest Simon; Deogratias, Emmanuel (International Journal of Research in Mathematics Education, 2024)
This research investigates the influence of peer groups on students' academic performance in mathematics courses at the university level, with a specific focus on Morogoro Municipality. The study aims to understand the dynamics of peer interaction and its impact on students' mathematical learning outcomes. A mixed-methods approach was employed, combining quantitative analysis of academic performance data with qualitative exploration of peer group dynamics through interviews and surveys. Encompassing all students in higher education institutions in Morogoro Municipal, the study includes a sample of 200 students randomly selected from four universities. Data collection methods involved questionnaires and interviews to glean insights into peer interaction patterns, academic performance, and demographic characteristics. Quantitative data collected undergo coding and Chi-square computation, facilitated by the Statistical Package for the Social Sciences (SPSS) version 20, enabling researchers to discern correlations between peer dynamics and academic achievement. Findings suggest that peer groups play a significant role in shaping students' attitudes, study habits, and academic achievement in mathematics. Positive peer interactions foster collaboration, motivation, and deeper understanding of mathematical concepts, leading to improved performance. Conversely, negative peer influences, such as social distractions and peer pressure, can hinder academic progress. Understanding the mechanisms through which peer groups influence academic performance can inform educational interventions and support systems aimed at enhancing mathematical learning outcomes at the university level.